Infodemic and Economic Fact Analysis at COVID-19 Crisis: Developing Country Perspective - Rahaman, Arafatur (Journal of Economics and Behavioral Studies, 2021)
Although COVID-19 prevention is effective through social management, long-term implementation of lockdown has resulted in unemployment, an economic downturn, disrupting casual social activities, and creating anarchy. It is difficult to answer the question “Health or Economy” directly, especially for developing countries like Bangladesh. The researcher’ tried to excavate how people responded with the misinformation and harmful aspects of improvident information on this pandemic accompanied by the economic crisis. The impending recession could be avoided by setting economic priority and effective policy response for the poor and vulnerable segment of the population. In this paper, the researcher used nethnography, shadow observation, and focus group discussion by video conferencing along with content analysis of print and electronic media to gain insights into the study. This paper will help governments and their partners to understand how the communities acted upon their communications and to prioritize contingency measures in crisis and post-crisis recession.